Coastal and Marine Tourism Monitoring System Design using Rapid Application Development (RAD) - Singgalen, Yerik Afrianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
To achieve sustainable tourism, a monitoring system of tourism activities is needed to minimize the environmental impact of the intensity of tourist visit activities. The development of coastal tourism needs particular attention, considering the diversity of activities around the coast related to environmental sustainability, including coral reefs. This study designed an information system and database to monitor coastal tourism activities to minimize the risk of damage to the coastal environment due to tourism activities. The method used in system design is Rapid Application Development (RAD), which has the following stages: requirement planning, user design, construction, and cutover. Meanwhile, the system and database design context is adjusted to the tourist destinations of Luari Beach, North Halmahera Regency, North Maluku Province, Indonesia. The results of this study show that identifying user needs at the requirements planning stage shows the need for a database of tourists visiting the destination and data related to the vehicles used. There is a need for a database related to beach conditions or beach environments and data on people involved as small entrepreneurs around coastal tourist areas. Considering the user's needs, at the user design stage, a prototype design is carried out using Oracle Apex with a dashboard display according to the data needed. At the construction stage, database configuration is carried out to display data visualization so that managers of beach tourist destinations understand the context and priority. System features and functions are tested at the cutover stage to evaluate application performance. The cutover result shows that successful applications can be used in decision-making. Thus, tourism destination managers take infrastructure development policies following existing conditions and short-, medium-, and long-term development plans.